Pirolisis Katalitik Tandan Kosong Sawit Menjadi Bio-oil dengan Katalis HZSM-5 - Sunarno Sunarno (Eksergi)
One of the alternative new energy sources is biomass. Biomass can be processes to produce bio-oil. The pyrolysis method was used to convert the palm empty fruit bunch from biomass to bio-oil. The purpose of this research are to study the influence of pyrolysis temperature with bio-oil yield and its properties. Pyrolysis process in slurry reactor with 50 grams palm empty fruit bunch, 500 ml thermo-oil and 2% HZSM-5 catalyst. Operating temperature variation (290,300,310 dan 3200 C) have been done. The result show that the optimum temperature obtained at 3200 C with bio-oil yield is 73.6%. The characterization result of bio-oil product are density is 1.008 gr/ml, viscosity is 12.63 cp, flash point 490 C, and maximum of component obtained is acetic acid with 47.09%.